2018
DOI: 10.12659/msm.909403
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Changes in Splanchnic Hemodynamics and Risk Factors of Portal Venous System Thrombosis After Splenectomy with Periesophagogastric Devascularization

Abstract: BackgroundThe purpose of this study was to investigate splanchnic hemodynamic changes and determine an optimal cutoff value for risk factors of portal venous system thrombosis (PVST) after splenectomy with periesophagogastric devascularization (SPD) in cirrhotic patients with esophageal and gastric variceal bleeding (EGVB) and portal hypertension (PH).Material/MethodsData on patients who underwent SPD were collected retrospectively from January 2013 to December 2017. Color Doppler ultrasound was performed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Liver function improvements may be due to the changes of splanchnic haemodynamics, namely, decrease of flow and velocity in portal vein and increase of flow and velocity in hepatic artery. 23 The decrease of total bilirubin after operation could result from the cessation of haemolytic reaction that occurs in the splenic parenchyma owing to hypersplenism. In addition, the reduction in total bilirubin could reflect a better functional hepatic reserve following the decrease of portal pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver function improvements may be due to the changes of splanchnic haemodynamics, namely, decrease of flow and velocity in portal vein and increase of flow and velocity in hepatic artery. 23 The decrease of total bilirubin after operation could result from the cessation of haemolytic reaction that occurs in the splenic parenchyma owing to hypersplenism. In addition, the reduction in total bilirubin could reflect a better functional hepatic reserve following the decrease of portal pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of AST and total bilirubin decreased and albumin increased with a statistical difference 1 year after surgery. Liver function improvements may be due to the changes of splanchnic haemodynamics, namely, decrease of flow and velocity in portal vein and increase of flow and velocity in hepatic artery 23 . The decrease of total bilirubin after operation could result from the cessation of haemolytic reaction that occurs in the splenic parenchyma owing to hypersplenism.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the anatomical structure and some morphogeometrical parameters (e.g., the diameter and curvature of the SV, and the distance between the IMV and splenoportal junction) of the PVS can significantly affect postoperative ALS and associated risk of postsplenectomy thrombosis. The marked increase in postoperative ALS associated with 'C'(+) variation may provide biomechanical evidence for explaining the clinical observation that patients with a larger diameter of the SV were at increased risk of developing thrombosis after splenectomy (Danno et al, 2009;Kinjo et al, 2010;de'Angelis et al, 2017;Huang et al, 2018). However, clinical studies on the correlations between the anatomical structure or other morphogeometrical features of the PVS and the risk of postsplenectomy thrombosis remain absent.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, some studies turned to investigating other factors that are related to hemodynamic conditions in the portal venous system (PVS). For instance, it was found that patients with a larger diameter of the splenic vein (SV) or the portal vein (PV) had a higher risk of developing postsplenectomy thrombosis (Danno et al, 2009;Kinjo et al, 2010;de'Angelis et al, 2017;Huang et al, 2018). The study by Huang et al (2018) further demonstrated that a higher preoperative flow rate in the PV was an independent risk factor of postsplenectomy thrombosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation